The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1590/18069657rbcs20170191
|View full text |Cite
|
Sign up to set email alerts
|

Reversibility of the Hardening Process of Plinthite and Petroplinthite in Soils of the Araguaia River Floodplain under Different Treatments

Abstract: ABSTRACT:Although ferruginous materials occur frequently in soils of tropical regions, information about the reversal of the hardening process of these materials is scarce. This study assessed the influence of different chemical treatments and periods of immersion on the reversibility of the hardening process of plinthite and petroplinthite in soils of the Araguaia River plain. Soil samples were collected from the plinthic horizons in 0.10 m high and 0.15 m diameter PVC cylinders and divided into subsamples wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…However, at the P3 observation point, the plinthite horizon properties (colored red at depth > 100 cm) were found. Martins et al (2018) stated that plinthite could be found in flat or slightly sloping areas, has high Fe, and is often exposed to seasonal groundwater levels. Plintithe is formed from the accumulation of iron hydroxide, quartz, and kaolinite.…”
Section: Soils Classification In Ayer Hitam Forest Reservementioning
confidence: 99%
See 1 more Smart Citation
“…However, at the P3 observation point, the plinthite horizon properties (colored red at depth > 100 cm) were found. Martins et al (2018) stated that plinthite could be found in flat or slightly sloping areas, has high Fe, and is often exposed to seasonal groundwater levels. Plintithe is formed from the accumulation of iron hydroxide, quartz, and kaolinite.…”
Section: Soils Classification In Ayer Hitam Forest Reservementioning
confidence: 99%
“…The presence of iron in the plintithe is due to anaerobic water conditions. The iron ion content is transported, and precipitation occurs, forming soft clayey iron oxide, which hardens after drying (Martins et al 2018). Almost all soil profiles (P1 to P5) at a depth of more than 100 cm showed evidence of clay eluviation due to the lessivage process.…”
Section: Soils Classification In Ayer Hitam Forest Reservementioning
confidence: 99%